2016
DOI: 10.3389/fpls.2016.00153
|View full text |Cite
|
Sign up to set email alerts
|

New Challenges for the Design of High Value Plant Products: Stabilization of Anthocyanins in Plant Vacuoles

Abstract: In the last decade plant biotechnologists and breeders have made several attempt to improve the antioxidant content of plant-derived food. Most efforts concentrated on increasing the synthesis of antioxidants, in particular anthocyanins, by inducing the transcription of genes encoding the synthesizing enzymes. We present here an overview of economically interesting plant species, both food crops and ornamentals, in which anthocyanin content was improved by traditional breeding or transgenesis. Old genetic stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 91 publications
0
79
0
1
Order By: Relevance
“…The AN1-AN11-PH4 triumvirate is also required for the stability of anthocyanins in the vacuole, as in certain genetic backgrounds ph4 and specific an1 alleles (formerly known as ph6 alleles) trigger the complete disappearance of anthocyanins and "fading" of the flower color after opening of the bud (de Vlaming et al, 1982(de Vlaming et al, , 1983Quattrocchio et al, 2006;Passeri et al, 2016). Fading is not triggered by the pH shift alone because it is not seen in ph5 and ph2 mutants but seems due to a different vacuolar defect caused by the misregulation of distinct AN1-AN11-PH4 target genes (Quattrocchio et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AN1-AN11-PH4 triumvirate is also required for the stability of anthocyanins in the vacuole, as in certain genetic backgrounds ph4 and specific an1 alleles (formerly known as ph6 alleles) trigger the complete disappearance of anthocyanins and "fading" of the flower color after opening of the bud (de Vlaming et al, 1982(de Vlaming et al, , 1983Quattrocchio et al, 2006;Passeri et al, 2016). Fading is not triggered by the pH shift alone because it is not seen in ph5 and ph2 mutants but seems due to a different vacuolar defect caused by the misregulation of distinct AN1-AN11-PH4 target genes (Quattrocchio et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To date, seven such PH genes have been identified in petunia via mutants that all show a similar phenotype: petals with a bluish color and an increased pH of petal homogenates (de Vlaming et al, 1983;van Houwelingen et al, 1998). Molecular analysis revealed that ph6 mutants represent specific an1 alleles that lost the capacity to acidify the vacuole but can still drive anthocyanin biosynthesis (Spelt et al, 2002) and that PH5 and PH1 are direct target genes of the AN11-AN1-PH4 complex that encodes two interacting P-ATPase transmembrane transporters that reside in the tonoplast (Verweij et al, 2008;Faraco et al, 2014).The AN1-AN11-PH4 triumvirate is also required for the stability of anthocyanins in the vacuole, as in certain genetic backgrounds ph4 and specific an1 alleles (formerly known as ph6 alleles) trigger the complete disappearance of anthocyanins and "fading" of the flower color after opening of the bud (de Vlaming et al, 1982(de Vlaming et al, , 1983Quattrocchio et al, 2006;Passeri et al, 2016). Fading is not triggered by the pH shift alone because it is not seen in ph5 and ph2 mutants but seems due to a different vacuolar defect caused by the misregulation of distinct AN1-AN11-PH4 target genes (Quattrocchio et al, 2006).…”
mentioning
confidence: 99%
“…Anthocyanin identification is critical in adulteration and profiling [349,350] studies and in evaluating the quality of crude and processed food. The design of plant products with a high added value allows increasing the synthesis [351] of plant-derived food antioxidants and in particular anthocyanins. In an effort to expand the palette of natural organic colourants (colour additives of food and beverage products), the food industry has launched a search for new products, for example blue colourants [352,353].…”
Section: Final Commentsmentioning
confidence: 99%
“…Potato can also have pigmented tuber skin and flesh, sprouts, leaves and stems. Anthocyanins in potato tuber skin and flesh are not only serving as a genetic model but, just like in other anthocyanin-rich crops and vegetables, enhance the market value of the plant by increasing its visual appeal to the consumer, reducing softening, shrivelling and fungal rots (Passeri et al 2016). What is also important, plant products rich in anthocyanins are health-promoting components of the human diet.…”
Section: Introductionmentioning
confidence: 99%
“…What is also important, plant products rich in anthocyanins are health-promoting components of the human diet. The health benefits associated with anthocyanins intake include: prevention of the degenerative diseases and cancer, reduction of retinal damage, decreasing inflammatory markers expression, reduction of risk of type-2 diabetes and reduction of weight gain (Passeri et al 2016).…”
Section: Introductionmentioning
confidence: 99%